Physical properties and localization investigations associated with the 2003 Mars Exploration rovers - Arvidson, R. E.; Anderson, R. C.; Haldemann, A. F. C.; Landis, G. A.; Li, R.; Lindemann, R. A.; Matijevic, J. R.; Morris, R. V.; Richter, L.; Squyres, S. W.; Sullivan, R. J.; Snider, N. O. (Journal of Geophysical Research. E. Planets, 2003)
A number of physical properties experiments will be conducted during the NASA 2003 Mars Exploration Rover Mission as the two vehicles explore Meridiani Planum and the floor of Gusev Crater. The investigations will include quantifying dust accumulation and dispersal dynamics by periodically monitoring the rover decks with the Athena Pancam and Mini‐TES instruments. Properties of soil‐like materials will be inferred from analyses of wheel track patterns, depths, and wheel slippage dynamics during traverses. The rovers will be modeled as dynamic mechanical systems to extract along‐track terrain topography and physical properties from times series of rover tilt vectors, wheel encoder counts, azimuths, motor currents, and rocker and bogie angles. Trenches will be excavated using rover wheels to characterize mechanical properties of soil‐like materials with depth and to expose subsurface materials for remote and in situ observations using the Athena Payload. The Rock Abrasion Tools will be used to expose rock subsurfaces for detailed analyses. Motor currents and penetration magnitudes will be compared to a database of rocks excavated by an engineering model of the Rock Abrasion Tool to understand Martian rock mechanical properties. Image‐based localization analyses will be pursued to better understand rover traverse directions and magnitudes and thus rover locations as a function of time. The physical properties and localization investigations, when combined with analyses of the full ensemble of Athena observations, will greatly improve our understanding of Martian surface properties and provide significant technology lessons for future landed missions.